Die Andere Reise : Afrika und die Diaspora. - Davis-Sulikowski, Ulrike; Denk, Wolfgang; Ferrero-Waldner, Benita; Mittringer, Markus; Njami, Simon; Vranitzky, Franz (Krems : Kunsthalle Krems, 1996)
Benjamin, Mario ; Bester, Willie ; Bethe-Selassié, Mickaël ; Bidjocka, Bili ; Botha, Andries ; Cabral, Francisco ; Castro, Humberto ; Clark, June ; Damoison, David ; Douglas-Camp, Sokari ; Fani-Kayode, Rotimi ; Konaté, Abdoulaye ; Lamothe, Frantz ; Latamie, Marc ; Read, Marcos Lora ; M'Bengue, As ; Ntakiyica, Aimé ; Pédurand, Bruno ; Olazábal, Santiago Rodriguez
biografie
Die Andere Reise : Afrika und die Diaspora, Kunsthalle Krems, 14. April bis 30. Juni 1996
Duits & Engels
boek
Keywords: Afrika